Technology-Based Collaborative Learning for Developing the Dynamic Concept of the Angle - Nimer Baya'a; Wajeeh Daher; Samah Mahagna (Emerging Science Journal, 2022)
This research intends to investigate the effect of collaborative computerized learning using GeoGebra on the development of the concept images of angle among seventh graders who were engaged in computerized collaborative activities that encouraged the development of five types of angle concept images: verbal, authentic-life, graphical, numeric, and dynamic. The research sample consisted of eight seventh grade students who worked collaboratively in groups of two. Two tests (a pre-test and a post-test) were administered to examine the development of students’ conceptual images of the angle. In addition, interviews were held with the participants to study this development. The Constant Comparison Method was used to analyze the data. The results showed positive effects of the visual and dynamic use of GeoGebra, as well as of the collaborative learning, on the development of participants' concept images of the angle, especially the dynamic one. The research results point to the importance of integrating dynamic tools into the teaching and learning of mathematics. Doi: 10.28991/ESJ-2022-06-01-09 Full Text: PDF